Value systems in a changing culture - Bender, Nathan Judson (Journal of religion and health, 1973)
ConclusionWe may be experiencing the last gasps of a once brilliant culture that is worn out and dying. Indeed, it seems to have a subconscious death wish, but the end is nowhere in sight. We may have to spend a little more time in this transitional period before the dominant sensate culture is balanced by a culture that will not disavow sensory truth, but that will rediscover the truth of faith with God as the center. Then and only then will the new day come to birth. Call it Idealistic (Sorokin) or the Age of Aquarius, or whatever you will; it will be a time of spiritual perception and a time when destructive aggression will be changed to creative assertion for the good of all mankind.